Peranan Camat Dalam Pemberdayaan Masyarakat Di Kecamatan Rainis Kabupaten Kepulaun Talaud - Majampoh, Alwein; Rares, Joyce Jacinta; Kolondam, Helly (Sam Ratulangi University, 2016)
Abstract : The purpose of this study was to determime how camat rolein empowering communities in the districtRainis Talaud islands district. The method used is descriptive gualitative method. The focus of research includes: The subdistrict govermments to encourage public participation in delelopment planning in the district; role toguide the work units implementing the orogram/community developmend activities in the district; successfulresearch informants interviewd as many as 10 persons namely : 2 sub-district government officials, 2 villageheads 2, 2 Orang LMP members, two community leaders, and two villagers data collection technigues usedwere interviews. Data was analysed using qualitative descriptive analysis technigues-interactive model of Milesand Huberann. Based on the results of the study conclude : (1) role toencourage public participation indevelopment planning in the discussion forum of development planning in the district has done fairiy weill; (2)role to provide guidance to the working units of government and community organization in the district havebeen done fairily well ; (3) role in empowering communities through the role to supervise theprogram/community development activities whether perpetrated by units of government work and civil societyorganizations have also done fairly well. Based on these conciusions suggested : (1) let more active inmobilizing the community to engage in development planning at the vollage and sub-district; (2) let moreeffective coordination meeting forum/consultation on guidance to the work units that acted uponprogram/activities of people in the district pemerdayaan; (3) let improve the implementation ofmonitoring/pemantauan and reporting systems on a regular basis about the implementation ofprogram/community development activities in the district.Key words : The role of community empowerment.